PENGARUH PEMBERIAN BIOCHAR BATANG TEMBAKAU DAN MIKORIZA TERHADAP PRODUKTIVITAS TEMBAKAU (Nicotiana tabaccum) BESUKI NA– OOGST - Muhammad Pandu Winata; Agus Budinuljanto Zainul (Berkala Ilmiah Pertanian, 2020)
Tobacco plant (Nicotiana tabaccum) is plant commodity that has a high selling value. The tobacco cultivation process uses traditional cultivation techniques, so that the productivity of tobacco is still low. Adding a mixture of compositions to the planting media could be a solution to the cultivation technique improvement. Additional materials that can be given into the planting media are biochar and mycorrhizal fungi. Biochar has the advantage of making the soil moist, crumbly and sterile. Mycorrhizal fungi can play a role in helping and facilitating plant roots in absorbing minerals and nutrients from the soil. The purpose of this study was to determine the effect of the biochar from tobacco stem and mycorrhizal on the production of Besuki na-oogst tobacco. The study was conducted in a modified plastic house (green house) owned by PT. Tempu Rejo Balung, Jember, from June to September 2019. The experimental design used in this study was a factorial completely randomized design consisting of 2 factors with 3 replications. The first factor is biochar dose which consists of 4 levels, 0 g biochar (B0) as control, 250 g biochar/20 Kg Soil (B1), 500 g biochar/20 Kg Soil (B2), 750 g biochar/20 Kg Soil (B3) and the second factor is the dose Mycorrhiza with 4 levels, namely Control (M0), 165 spores mycorrhiza/plant (M1), 330 spores mycorrhiza/plant (M2), 165 spores mycorrhiza/plant (M3), so that there are 48 experimental units. Our results showed that: (1) there were interactions on the parameters of leaf wet weight, leaf dry weight and root volume. The best treatment is B3M3 with 89.66 g wet weight, 8.43 g dry weight and 386.67 ml root volume. (2) there is an effect of the treatment of biochar application on variable stem diameter and the giving of biochar 750 g (B3) is the best treatment with a diameter of 2.72 cm, (3) effect of mycorrhizal treatment on variable stem diameter and mycorrhizal giving of 165 spores mikoriza (M3) is the best treatment produces a diameter of 2.63 cm Keywords: Nicotiana tobaccum, Biochar, Mikoriza